Obesidade, inflamação e complicações metabólicas - Francisqueti, Fabiane Valentini [UNESP]; Nascimento, André Ferreira do; Corrêa, Camila Renata [UNESP] (My University, 2015)
The prevalence of obesity has increased in the past two decades. This growth has been attributed to changes in dietary habits, especially increased consumption of fats and sugars. It is clear that obesity is a risk factor for cardiovascular disease and insulin resistance, and the inflammatory process favors this context. Aim: To address the inflammatory aspects of obesity and associated metabolic complications. Data Sources: Original data from articles found through search of scientific databases. Summary of findings: Micro hypoxia, reticulum stress, and activation of toll-like receptor 4 are responsible for triggering inflammation in adipose tissue, which is the place where the process begins. Thus, there is an increased production of various adipokines, such as IL-6 and TNF-α, which impair insulin signaling pathway, leading to resistance to hormone, one of the first complications of obesity. From this, with the intensity of stimulation, the condition may worsen triggering type 2 diabetes and other comorbidities. Conclusion: Thus, the elucidation of the roles and mechanisms of the main adipokines lead to a better understanding of the pathogenesis of obesityrelated disorders.

A prevalência da obesidade tem aumentado durante as duas últimas décadas. Esse crescimento tem sido atribuído a mudanças no hábito dietético, principalmente maior consumo de gorduras e açúcares. É evidente que a obesidade é um fator de risco para doenças cardiovasculares e resistência insulínica, e o processo inflamatório favorece esse contexto. Objetivo: Abordar os aspectos inflamatórios da obesidade e as complicações metabólicas associadas. Fonte de dados: Artigos levantados por meio de pesquisa em base de dados. Síntese dos dados: A microhipóxia, o estresse do retículo e a ativação dos receptores toll-like 4 são responsáveis por desencadear a inflamação no tecido adiposo, sendo esse o local onde se inicia o processo. Dessa forma, há um aumento na produção de diversas adipocinas, como IL-6 e TNF-α, as quais prejudicam a via de sinalização da insulina, levando à resistência a esse hormônio, uma das primeiras complicações da obesidade. A partir disso, com a intensidade desse estímulo, o quadro pode agravar-se, desencadeando diabetes melito tipo 2 e outras comorbidades. Conclusão: Assim, aelucidaçãodas funçõese mecanismos de açãodas principais adipocinaslevará a umamelhor compreensãoda patogênesede desordensligadas àobesidade.
Obesity, inflammation and metabolic complications
Keywords: Obesity; Inflammation; Insulin resistance; Obesidade; Inflamação; Resistência à insulina